Verification of Kastner Visibility of Hilal Observation Results at Condrodipo Rukyat Center in 1444 H - Nur Faizah; Muhammad Muadz Dzulikrom (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
The Kastner Hilal visibility method is one of numerous contemporary observation techniques developed with the objective of monitoring the appearance of Hilal with greater precision. This paper presents a discussion of Hilal observations conducted at the Condrodipo Rukyat Center. The visibility results are analyzed using curve graphs, facilitating the assessment and validation of the observations. The findings demonstrate that employing the Kastner mathematical model can corroborate visibility with a substantial degree of concurrence, regardless of atmospheric constraints and sky conditions. However, the results of observer reports in the field are often inconsistent with model predictions, especially in conditions of low Hilal altitude and naked eye observations. Therefore, more rigorous scientific verification and reliable methodologies are needed to confirm observations for the integrity of the determination of the beginning of the lunar month.